NORMAL INTESTINAL FLORA OF LONG-TAILED MACAQUES IN MONKEY FOREST, UBUD, BALI - Imam Rahman; I Gede Soma; I Gusti Ketut Suarjana (Buletin Veteriner Udayana, 2025)
The long-tailed macaque (Macaca fascicularis) is a primate commonly found in Indonesia, including in the Monkey Forest Ubud, Bali. This primate has a high adaptability to its environment, including dietary patterns influenced by interactions with humans. The normal gut flora refers to organisms that live in the gastrointestinal system of the long-tailed macaque. This study aims to identify the normal bacteria present in the intestines of long-tailed macaques in the Monkey Forest Ubud. The method used was an observational cross-sectional study. Samples were collected by rectal swabbing using sterile cotton swabs, with a total of 15 samples. Bacterial isolation and identification were performed using Sheep Blood Agar, Nutrient Agar, and MacConkey Agar media. Bacterial identification included primary tests and biochemical tests such as Triple Sugar Iron Agar, Sulfide Indole Motility, Methyl Red-Voges Proskauer, and Simmons Citrate Agar. The results of the study revealed three types of bacteria identified: Escherichia coli, Streptococcus sp., and Staphylococcus sp. Further identification using molecular methods is necessary to determine the bacterial species more specifically. Additionally, further research could be conducted to explore the presence of other bacteria that may inhabit the intestines of the long-tailed macaque.